COMMUNITY EMPOWERMENT IN THE UTILIZATION OF RHIZOME SPICES AS TRADITIONAL BEVERAGES IN SUKA KARYA VILLAGE, JAMBI CITY - Rahmah, Rahmah; Supriadi, Supriadi; Rusdi, Mesa Sukmadani (Universitas Jambi, 2025)
The utilization of rhizome spices such as turmeric (Curcuma domestica) and ginger (Zingiber officinale) in the community is generally limited to culinary seasoning, whereas both have great potential as traditional beverages beneficial for health. This community service activity aimed to enhance the knowledge and skills of residents in Suka Karya Village, Jambi City, in processing rhizome spices into traditional beverages with both health and economic value. The implementation method included participatory discussions and training, conducted on September 5, 2025, at the Suka Karya Village Office with 25 participants, consisting of PKK women cadres, neighborhood heads (RT), Babinsa, village staff, and local residents. The results showed that by the end of the program, participants were able to describe the benefits of turmeric and ginger as well as practice the preparation of traditional beverages such as jamu kunyit asam and wedang jahe. In conclusion, this community empowerment program successfully improved residents’ understanding and skills in utilizing rhizome spices for health while simultaneously opening opportunities for household businesses based on local wisdom. Keywords: Community empowerment, turmeric, ginger, traditional drinks.